Driving Success Through SIM: A Critical Analysis Management information Systems Influence on Decision-Making Processes - Rafli, Moh (Journal of Business Management and Economic Development, 2024)
In this journal, we explore the influence of Systems Information Management (SIM) on decision-making processes in organizations. The aim is to conduct a critical analysis of the contribution of SIM in increasing the effectiveness of decision making. The research method used is literature analysis from various sources such as scientific journals and related articles. The results show that effective implementation of SIM can speed up the decision-making process, increase information accuracy, and enable managers to make more timely decisions. In conclusion, SIM plays a vital role in organizational success through informed decision making. The implications of this research emphasize the importance of continuing to improve SIM implementation to support better decision-making processes in facing increasingly complex business challenges. The results of this study can provide valuable insights for practitioners and researchers in the field of information management.